SISTEM INFORMASI MANAJEMEN HUBUNGAN PELANGGAN PADA PT. XYZ PALEMBANG - Fransisca Fransisca; Imelda Imelda2; Dafid Dafid (Jurnal TAM (Technology Acceptance Model), 2017)
PT. XYZ is distributor and sales of mobile phone in Palembang city. PT. XYZ is not maximal for giving services to customers where it need more time in purchase order and sale products . There’s no easiness in interaction process between customer and company where company when interacting with customers only by phone and face to face. Information delivery about products, promotions, customers critique and suggestions can not informed quickly. For customer data management by this day can not used and maximized for analysing customers needs and customers purchase behaviors. In the development of this system use Iteration methodology with PHP language programming and MySQL database. The system that is being develop has feature like product order, purchase, critique and suggestions, and live chat that make communication more communicative and interactive. These system also generates customers report, best customers report, transactions report, and best sales product report. The result of this research is a design of customer relationship management system that easier PT. XYZ to manage relationship to customer